Heterogeneity of tissue IL-17 and tight junction proteins expression demonstrated in patients with autoimmune thyroid diseases. Issue 25 (June 2018) - Zake, Tatjana; Skuja, Sandra; Kalere, Ieva; Konrade, Ilze; Groma, Valerija
Abstract : Abstract: Th17 cells together with their hallmark cytokine interleukin (IL)-17 were identified as crucial contributing factors in the pathogenesis of thyroid autoimmunity. The cytokine-regulated tight junction (Tj) disruption is thought to be essential in the initiation and/or development of several diseases. Still, the role of IL-17 maintaining Tj integrity in autoimmune thyroid diseases (AITDs) has not yet been evaluated. We aimed to investigate integrity of the thyroid follicle by studying immunoexpression of cellular Tj – zonula occludens (ZO)-1 and claudin-1 proteins coupled to IL-17A and CD68 detection in AITD patients compared with controls. Thirty-five adult patients undergoing thyroidectomy and presenting 18 cases of Hashimoto thyroiditis (HT), 7 of Graves' disease (GD) as well as 10 subjects of colloid goiter without autoimmune component served as controls were enrolled in this study. An immunohistochemical analysis including IL-17A, ZO-1, claudin-1, and CD68 detection was performed in each case. The correlation of IL-17A with Tj and CD68 in patients with AITD was also analyzed. Apart from inflammatory cells, we evidenced a stronger expression level of IL17A in the thyroid follicular cells in HT patients when compared with GD or colloid goiter. A significant reduction of ZO-1 immunoreactivity was observed in the thyrocytes in HT patients, whereas no significant differences were found in claudin-1 expression in HT and GD compared with colloid goiter patients. A significantly higher number of thyroid follicles with CD68-positive cells was found in HT patients than that in patients with GD or colloid goiter. In HT patients, the expression of IL-17A in the follicular cells was positively correlated with CD68 immunopositivity, whereas no association with claudin-1 or ZO-1 expression was found. GD patients did not reveal any significant correlation of IL-17A with Tj and CD68. Strong overexpression of IL-17A observed in the thyroid epithelial cells is associated with the presence of intrafollicular CD68-positive cells in HT patients. We evidenced the changes in molecules of thyrocyte junctional complexes highlighting impairment of the thyroid follicle integrity in HT, but no association with IL-17A was found.